2007
DOI: 10.1016/j.ejvs.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Clinical Trial of the Duration of Compression Therapy after Varicose Vein Surgery

Abstract: We found no benefit in wearing compression stockings for more than one week following uncomplicated high saphenous ligation with stripping of the great saphenous vein with respect to post-operative pain, number of complications, time to return to work, or patient satisfaction for up to 12 weeks following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 10 publications
(8 reference statements)
0
59
0
3
Order By: Relevance
“…Systematic review of the literature identified 183 potential studies, of which 161 were discounted as ineligible after title and abstract review. After full‐text review of the remaining 22 papers, seven were eligible for inclusion ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Systematic review of the literature identified 183 potential studies, of which 161 were discounted as ineligible after title and abstract review. After full‐text review of the remaining 22 papers, seven were eligible for inclusion ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis included seven RCTs, of which the primary treatment was open conventional surgery in three studies, UGFS in two studies and EVLA in two ( Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations